Efficacy of a virtual reality-based intervention in children with medulloblastoma: Case series - Tanrıverdi, Müberra; Çakır, Fatma Betül; Karantay Mutluay, Fatma (Asociacion Espanola de Pediatria, 2023)
[Abstract Not Available]
Eficacia de una intervención basada en realidad virtual en niños con meduloblastoma: Serie de casos
Keywords: Medulloblastoma; Case Series; Virtual Reality-Based